Regulations For Active Tni Members Occupiing Civilian Positions From The Perspective Of Statutory Regulations - Mayga Harvin; A. Zarkasi; Aswari Hepni (International Journal of Multidisciplinary Sciences and Arts, 2026)
The placement of active members of the Indonesian National Armed Forces (TNI) in civil service positions has resurfaced as a debated issue within Indonesia's post-reform constitutional dynamics. Normatively, Law Number 34 of 2004 concerns the Indonesian National Armed Forces limits the placement of active soldiers to specific ministries and agencies to maintain military professionalism and the principle of civilian supremacy. However, recent developments through Law Number 3 of 2025 regarding the Amendment to Law Number 34 of 2004 have expanded the scope of civil service positions accessible to active TNI personnel. Furthermore, practical implementation shows instances of active soldiers being placed in civil positions beyond the prevailing statutory provisions. This research aims to analyze the legal regulations regarding the placement of active TNI members in civil service positions and its implications for the principles of TNI professionalism and civilian supremacy in a democratic state. This study utilizes a normative legal research method with a statutory approach, a conceptual approach, and a historical approach. The results indicate that while the regulations for placing active TNI personnel are clearly delineated in the TNI Law and related regulations, the practice of placing active soldiers outside these provisions creates potential conflicts of norms, undermines the principle of civilian supremacy, and threatens the professionalism of the military institution. Consequently, the enforcement of legal certainty and the strengthening of oversight mechanisms are essential to ensure that the placement of TNI personnel in civil positions remains aligned with the principles of the rule of law and democracy.